2021
DOI: 10.3390/ph14050418
|View full text |Cite
|
Sign up to set email alerts
|

Polyvinyl Alcohol-Based 3D Printed Tablets: Novel Insight into the Influence of Polymer Particle Size on Filament Preparation and Drug Release Performance

Abstract: Three-dimensional printing (3DP) by fused deposition modeling (FDM) has gained momentum as a promising pharmaceutical manufacturing method due to encouraging forward-looking perspectives in personalized medicine preparation. The current challenges the technology has for applicability in the fabrication of solid dosage forms include the limited range of suitable pharmaceutical grade thermoplastic materials. Hence, it is important to investigate the implications of variable properties of the polymeric carrier on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 58 publications
2
12
0
Order By: Relevance
“…The XRPD pattern of the PVA polymer (Figure 5b), with a broad diffraction peak at 19.3° (2θ), confirms its semi-crystalline nature [34,36,37]. The sorbitol showed multiple The XRPD pattern of the PVA polymer (Figure 5b), with a broad diffraction peak at 19.3 • (2θ), confirms its semi-crystalline nature [34,36,37]. The sorbitol showed multiple sharp diffraction peaks, the most intense of which were at 11.6 • , 18.6 • , and 25.4 • (2θ), representative of its crystalline structure [36,52].…”
Section: X-ray Powder Diffraction (Xrpd)mentioning
confidence: 65%
See 1 more Smart Citation
“…The XRPD pattern of the PVA polymer (Figure 5b), with a broad diffraction peak at 19.3° (2θ), confirms its semi-crystalline nature [34,36,37]. The sorbitol showed multiple The XRPD pattern of the PVA polymer (Figure 5b), with a broad diffraction peak at 19.3 • (2θ), confirms its semi-crystalline nature [34,36,37]. The sorbitol showed multiple sharp diffraction peaks, the most intense of which were at 11.6 • , 18.6 • , and 25.4 • (2θ), representative of its crystalline structure [36,52].…”
Section: X-ray Powder Diffraction (Xrpd)mentioning
confidence: 65%
“…However, the XRPD pattern of the filament was attenuated, confirming the complete amorphization of the HPMCAS-HG and magnesium stearate during extrusion. The XRPD pattern of the PVA polymer (Figure 5b), with a broad diffraction peak at 19.3° (2θ), confirms its semi-crystalline nature [34,36,37]. The sorbitol showed multiple The XRPD pattern of the PVA polymer (Figure 5b), with a broad diffraction peak at 19.3 • (2θ), confirms its semi-crystalline nature [34,36,37].…”
Section: X-ray Powder Diffraction (Xrpd)mentioning
confidence: 74%
“…Goyanes et al studied the release of fluorescein in tablets with different infills and found that the lower the filling of the tablet, the higher the percentage of fluorescein released [37]. Other studies also support these results [26,38]. As can be seen in Figure 5, none of the infills below 10% allowed maximal strength.…”
Section: Influence Of Infill On Strengthmentioning
confidence: 79%
“…In the physical mixture case, the melting point was similar to that of FDP. Nevertheless, the thermogram of the FDP-loaded PVA filament did not present the FDP melting peak, indicating the complete FDP incorporation into the PVA matrix [ 14 ].…”
Section: Resultsmentioning
confidence: 99%